1997 compensation report : executive, professional & managerial positions (HR Consulting Associates Port of SpainTT, 1998)
Analyses the 1997 compensation of jobs in 64 companies representing 7 major industry sectors in Trinidad and Tobago. Describes also, the incidence of and trends in bonus plans.
DC